STRATEGIES TO TACKLE DRUG ABUSE AMONG STUDENTS - Ika Zakiah; Entin Solihah; Cut Suraiya Wahyuni Utami (CV. Adiba Aisha Amira, 2025)
Drug abuse among students is a serious problem that requires attention and action from various parties. The method used is a literature study The results showed that eflective strategies include: (1) education and socialization of the dangers of drugs in schools, (2) strengthening the role of families in supervision and guidance, (3) improving law enforcement, (4) developing appropriate rehabilitation programs for students, and (5) utilizing technology for early detection and education. In conclusion, a multi-dimensional approach and cooperation between various parties are needed to address this problem. Consistent and sustainable implementation of these strategies is expected to significantly reduce the level of drug abuse among students.